Late maternity: the pregnancy and delivery in women after 35 years of age - Hincz, Piotr; Wojciechowska, Edyta; Podciechowski, Lech; Kubiak, Agnieszka; Wilczyński, Jan (Menopause Review/Przegląd Menopauzalny, 2006)
Aim of study: The aim of the study was to assess the pregnancy and labour risk factors for pregnant women older than ≥35 years. Materials and methods: The study was carried out among 224 patient, 184 in the age group ≥35-39 and 40 in the age group ≥40 years who delivered in the Department of Maternal–Fetal Medicine, PMMH, between 21.01.2005 and 18.02.2006. The study was based on Access database including data of all departamental deliveries. We analyzed pregnancy and labour complications and newborn status (birthweight, Apgar score and pH from artery of umbilical cord). We specifically aimed to estimate the occurence of gestational diabetes, hypertension connected with pregnancy, fetal anomalies, rate of preterm deliveries, incidence of SGA and macrosomia, stillbirths rate and the percentage of cesarean section. We also analyzed the prepregnancy body weight and BMI and the weight gain during the pregnancy. Conclusions: In the group of patients older than 35 years with normal karyotype, the course of pregnancy is unremarkable in most cases and the perinatal outcome is good; gestational diabetes and hypertension are the most common complications of pregnancy; there is no significant difference in the incidence of SGA, macrosomia and preterm delivery; the rate of cesaren section, especially elective, is increased.